Role of Internal Control Systems and Organizational Culture in Preventing Village Fund Fraud: Evidence from Pineleng District, Minahasa Regency - Lidia Marlina Mawikere; Jenny Morasa; Peter Marshall Kapojos (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Village fund fraud has become a critical governance challenge in Indonesia, with cases reported across districts, including Minahasa Regency. Effective prevention requires examining both institutional mechanisms and cultural factors within village administrations. Objective: This study aims to analyze the influence of internal control systems and organizational culture on fraud prevention in village fund management in Pineleng District, Minahasa Regency. Methods: This study employs a quantitative approach with data collection conducted through questionnaires distributed to village officials. A total of 88 respondents, including village heads, village secretaries, village treasurers, Village Consultative Body (BPD) members, and section heads in Pineleng District, were selected using purposive sampling. Data were analyzed using multiple linear regression with SPSS Version 25. Results: The results indicate that the internal control system does not have a significant effect on village fund fraud prevention (t=0.428, sig.=0.670 > 0.05), whereas organizational culture has a positive and significant effect on fraud prevention (t=9.074, sig.=0.000 < 0.05). Simultaneously, both variables jointly influence fraud prevention (F=70.707, sig.=0.000), explaining 62.5% of the variance in fraud prevention (R²=0.625). Conclusion: The internal control system does not significantly prevent village fund fraud, while organizational cultureplays a positive and significant preventive role. Village governments are recommended to strengthen an organizational culture rooted in integrity and accountability and to revitalize internal control systems to move beyond mere administrative compliance toward substantive fraud prevention.